Individual and Occupational Characteristics to the Workload of Health Workers During the Covid-19 Pandemic - Suryono Suryono; Gunawan Pamudji Widodo; Tri Murti Andayani (Jurnal Ilmiah Kesehatan (JIKA), 2022)
The Covid-19 pandemic has had an impact on various aspects of life, one of which is the workload of health workers. This study aims to describe the workload of health workers and determine the relationship between the characteristics of the research subjects and the workload during the Covid-19 pandemic. This research is an analytic observational type with a Cross-Sectional approach, the instrument used is a workload questionnaire. Data were obtained from distributing questionnaires to health workers at health service facilities owned by the Government of Tana Tidung Regency, North Kalimantan in October 2021. The results showed that public health workers had the highest workload score of 26,8 ± 9,32 and physical therapy workers had the lowest workload score was 18,8 ± 4,55. The average score of the workload of health workers is 23,43 ± 5,81. The p-value of the Chi Square analysis between age and workload is 0,013. The workload of health workers in health care facilities during the Covid-19 pandemic is in the medium category. There is a significant relationship between the characteristics of the profession category/occupation and workload, the difference in the profession/occupation determines the level of workload.